Effect of Metarhizium anisopliae (Metsch.) Sorok. and Beauveria bassiana (Bals.) Vuill. on predatory mite Iphiseiodes zuluagai Denmark & Muma (Acari: Phytoseiidae) - Barreto, Rodrigo Soares; Marques, Edmilson Jacinto; Corrêa Gondim Junior, Manoel Guedes; Oliveira, José Vargas; Ferreira, Josinélia Fernandes; Santos Junior, Hugo José Gonçalves (BioAssay, 2011)
It was aimed at with this work to evaluate the selectivity of the isolated 645 and CG 321, of the fungus entomopathogenic Beauveria bassiana (Bals.) Vuill. and Metarhizium anisopliae (Metsch.) Sorok. respectively, in the concentration of 108 conidia/mL, on recently emerged females of Iphiseiodes zuluagai Denmark & Muma (Acari: Phytoseiidae), originating from of laboratory rearing. The research was developed at the Laboratory of Pathology of Insects of the Rural Federal University of Pernambuco (UFRPE), in Recife, in temperature of 26.5 ± 0.6º C and 78.4 ± 4.2% of UR and fotofase of 12h. The percentage of total mortality provoked by the isolated 645 of B. bassiana was of 35.94% and the confirmed mortality was of 32.81%. Regarding isolated CG 321 of M. anisopliae, the percentage of the total mortality 42.19% and confirmed 35.94%. With base in the obtained results, it can be conclude that both isolated tested 645 and CG 321 showed pathogenic for the mite at laboratory level; however the isolated 645 of B. bassiana showed smaller numeric values of virulence, showing certain selectivity to this mite predator, showed as an alternative for use in programs of biological control.